Fabrication of a Sustainable Charcoal-Fired Crucible Furnace for Recycling Aluminum Waste Cans - Taiwo, Oluwaseyi Omotayo; Ebuka, Christopher; Ori, Samuel Isaac; Onyebuchi, Edeh Isaac; Izunwanneka, Shimobi Nelson; Uchennaya, Onwe Joseph (Indo Green Journal, 2025)
Aluminum recycling is a vital process in minimizing environmental degradation and conserving energy. This paper presents the design, fabrication, and performance evaluation of a charcoal-fired crucible furnace specifically constructed for melting aluminum waste cans. The project aims to promote local recycling efforts by offering a cost-effective and energy-efficient solution using locally available materials. The furnace was constructed using mild steel, fire bricks, refractory cement, and insulation materials. The crucible was made from graphite-clay composite. Performance evaluation showed that the furnace reached a temperature of 750°C within 25 minutes, melting aluminum efficiently with an average recovery rate of 85%. This design offers a sustainable and scalable solution for small- to medium-scale aluminum recycling operations, particularly in developing countries.